Civil liberties under siege: the U.S. federal government and the anti-Stalinist left, 1941-1958 - Tiplady, John (2017)
The anticommunist political repression of the 1940s and 1950s was predicated on the claim that the Communist Party was a menace to national security because of its ties to the Soviet Union. In reality federal repression targeted a broad a swathe of radicals. One consequence not fully appreciated at the time, but detailed in this study, was the deliberate destruction of the anti-Stalinist left, an independent sector of the American left most critical of Stalinist Communism. Complementing recent scholarship that has addressed some aspects of this process, this thesis is the first comprehensive examination of the federal campaign to crush the anti-Stalinist left, assessing its significance for American political history. Anti-Stalinist radicals posed little threat to national security, yet during World War II and the early Cold War the state subjected them to harassment, intimidation, imprisonments, job losses, travel restrictions, and deportations. In order to understand why they were targeted, this thesis explores the motivations of government officials, who engaged in a sustained assault on democratic liberties. By the end of the 1950s, the anti-Stalinist left was a shadow of its former self, cut off from the working class communities that were central to its program. Meanwhile, in exaggerating security threats, federal officials justified the establishment of a national security state with powerful mechanisms of political control, permanently altering the political landscape of the United States. The story of the U.S. federal government and the anti-Stalinist left enhances our understanding of the politics of the age of “liberal consensus,” achieved more coercively than that term suggests.